Moving Beyond Average Values: Assessing the Night-To-Night Instability of Sleep and Arousal in DSM-IV-TR Insomnia Subtypes - Sánchez-Ortuño, M. Montserrat (Associated Professional Sleep Societies, LLC, 2011)
STUDY OBJECTIVES: We explored differences between individuals with DSM-IV-TR diagnoses of primary insomnia (PI) and insomnia related to a mental disorder (IMD) by using serial measurements of self-reported sleep variables (sleep onset latency, SOL; wake after sleep onset, WASO; total sleep time, TST; sleep efficiency, SE), and visual analogue scale ratings of 2 forms of bedtime arousal (cognitive and emotional). Furthermore, we sought to examine the relationship between sleep and arousal within each diagnostic subgroup. DESIGN: Between-group and within-group comparisons. SETTING: Duke and Rush University Medical Centers, USA. PARTICIPANTS: One hundred eighty-seven insomnia sufferers (126 women, average age 47.15 years) diagnosed by sleep specialists at 2 sleep centers as PI patients (n = 126) and IMD patients (n = 61). INTERVENTIONS: N/A MEASUREMENTS AND RESULTS: Multilevel models for sleep measures indicated that IMD displayed significantly more instability across nights in their TST (i.e., larger changes) than did PI patients. With respect to pre-sleep arousal, IMD patients exhibited higher mean levels of emotional arousal, as well as more instability on the nightly ratings of this measure. Within the PI group, correlational analyses revealed a moderate relationship between the 2 arousal variables and SOL (r values 0.29 and 0.26), whereas the corresponding correlations were negligible and statistically nonsignificant in the IMD group. CONCLUSIONS: We found a number of differences on nighttime variables between those diagnosed with primary insomnia and those diagnosed with insomnia related to a mental disorder. These differences imply different perpetuating mechanisms involved in their ongoing sleep difficulties. Additionally, they support the categorical distinctiveness and the concurrent validity of these insomnia subtypes. CITATION: Sánchez-Ortuño MM; Carney CE; Edinger JD; Wyatt JK; Harris A. Moving beyond average values: assessing the night-to-night instability of sleep and arousal in DSM-IV-TR insomnia subtypes. SLEEP 2011;34(4):531-539